Redox chemistry of (Co4(CO)3([my] 3-CO)3([my] 3-C7H7)([eta]5-C7H9)) - reversible carbon−carbon coupling versus metal cluster degradation - Wadepohl, Hubert; Gebert, Stefan; Pritzkow, Hans (European journal of inorganic chemistry, 2000)
Chemical reduction of the tetracobalt cluster complex [Co4(CO)3(μ3-CO)3(μ3-C7H7)(η5-C7H9)] (3), followed by addition of [PPh4]Br, gives the complex [Co4(CO)3(μ3-CO)3(μ3-C7H7)2μ-η4:η4-(C7H9)2]2− as a mixture of two diastereomers [4A]2− and [4B]2− in high yield. The crystal structure of [4A]2−[PPh4]2·1.5C7H8 has been determined and confirms the reductive coupling of two Co4 cluster coordinated apical cycloheptadienyl rings to form a bridging bicycloheptyl-3,5,3′,5′-tetraene ligand. Reduction of 3 with Li[HBEt3] and subsequent treatment with aqueous [NnBu4]Cl results in the formation of [Co4(CO)3(μ3-CO)3(μ3-C7H7)(C7H10)]− [5]−. Addition of [(η-C6H6)Ru(NCMe)3][BF4]2 after the borohydride reduction gives [Ru(η-C6H6)Co3(CO)3(μ3-CO)3(μ3-C7H7)] (6), a product derived from reductive Co4 cluster degradation. A detailed electrochemical and spectro-electrochemical study of the redox behaviour of 3 and [4]2− has been carried out. The complex potential current response of 3 is rationalized in terms of the formation of the radical anion [3]− as the primary intermediate, which may be reversibly reduced further to give the much more stable [3]2− and then [3]3−. Dimerization of [3]− to give [4]2− occurs by formation of a new carbon−carbon bond between the apical C7H9 ligands. The two redox-active moieties in [4]2− behave as independent, non-interacting redox centres. The oxidized form 4 is unstable and dissociates back to 3 almost quantitatively, thus completing a redox cycle characteristic of a “molecular battery”. The homogeneous rate constant for dimerization has been evaluated as kDIM (2 [3]− → [4]2−) = 0.30 ± 0.05 mM−1 s−1.